Destinations of nursing and allied health graduates from two Australian universities: A data linkage study to inform rural placement models - Sutton, Keith; Depczynski, Julie; Smith, Tony; Mitchell, Eleanor; Wakely, Luke; Brown, Leanne J.; Waller, Susan; Drumm, Daniel; Versace, Vincent L.; Fisher, Karin; Beauchamp, Alison (The Australian journal of rural health, 2021)
Objective Combined, nursing and allied health constitute most of the Australian health workforce; yet, little is known about graduate practice destinations. University Departments of Rural Health have collaborated on the Nursing and Allied Health Graduate Outcomes Tracking to investigate graduate entry into rural practice. Design Data linkage cohort study. Setting Monash University and the University of Newcastle. Participants Graduates who completed their degree in 2017 across seven disciplines. Main outcome measure(s) The outcome variable was Australian Health Practitioner Regulation Agency principal place of practice data. Explanatory variables included discipline, age, gender, location of origin, and number and duration of rural placements. Result Of 1130 graduates, 51% were nurses, 81% females, 62% under 21 years at enrolment, 23% of rural origin, 62% had at least one rural student placement, and 23% had over 40 cumulative rural placement days. At the time of their second Australian Health Practitioner Regulation Agency registration, 18% worked in a ‘Rural principal place of practice.’ Compared to urban, rural origin graduates had 4.45 times higher odds ratio of ‘Rural principal place of practice.’ For graduates who had <20 cumulative rural placement days, compared to zero the odds ratio of ‘Rural principal place of practice’ was the same (odds ratio = 1.10). For those who had 20‐40 rural placement days, the odds ratio was 1.93, and for >40 rural placement days, the odds ratio was 4.54). Conclusion Rural origin and more rural placement days positively influenced graduate rural practice destinations. Outcomes of cumulative placements days may compare to immersive placements.